2008
DOI: 10.1017/s0033291708003279
|View full text |Cite
|
Sign up to set email alerts
|

Interrelated neuropsychological and anatomical evidence of hippocampal pathology in the at-risk mental state

Abstract: Our findings suggest progressive and interrelated structural-functional pathology of the hippocampus, as prodromal symptoms and behaviours accumulate, and the level of risk for psychosis increases. Given the inverse correlation of learning and memory deficits with social and vocational functioning in established schizophrenia, our findings substantiate the rationale for developing preventive treatment strategies that maintain cognitive capacities in the at-risk mental state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 49 publications
3
60
0
2
Order By: Relevance
“…Finally our finding of a left laterality of hippocampus abnormality is in line with some previous studies (Velakoulis et al, 1999(Velakoulis et al, , 2006, but not all (Hurlemann et al 2008). We believe that there are several reasons for the inconsistent results.…”
Section: Arms-nt)supporting
confidence: 94%
See 1 more Smart Citation
“…Finally our finding of a left laterality of hippocampus abnormality is in line with some previous studies (Velakoulis et al, 1999(Velakoulis et al, , 2006, but not all (Hurlemann et al 2008). We believe that there are several reasons for the inconsistent results.…”
Section: Arms-nt)supporting
confidence: 94%
“…The hippocampus as a key region of interest has been investigated in numerous studies at different stages of the disease (Lopez-Garcia et al, 2006;Nelson et al, 1998;Phillips et al, 2002;Steen et al, 2006;Velakoulis et al, 2006) and is among the most robust brain abnormalities found in schizophrenia (Seidmann et al, 2003;Knable et al, 2004). The hippocampus is of particular interest as it is highly interconnected with other brain regions, including the frontal lobe that has also been proposed to be important for schizophrenia (Honea et al, 2005;Hurlemann et al, 2008;Shenton et al, 2001). A meta-analysis found hippocampal volume (HV) reductions of about 4% in chronic schizophrenia (Nelson et al, 1998) and of about 2.7% in first-episode schizophrenia (Steen et al, 2006) compared to healthy controls (HC).…”
Section: Structural Brain Abnormalities In Schizophrenia Have Been Dementioning
confidence: 99%
“…18,19,22 Additional comparison of hippocampal volumes between ARMS and HC showed no significant difference as well. Reduced hippocampal volume is a frequent finding from regionof-interest studies in ARMS samples [47][48][49][50][51] and has been shown to be statistically significant at the whole-brain level in 1 VBM study, 4 although some inconsistences have also been reported. 52,53 The higher sensitivity of manual tracing methods to detect volumetric changes in medial temporal structures could explain our inability to replicate hippocampal volume reduction often reported by manually traced region-of-interest studies in ARMS samples.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with schizophrenia, associations between positive psychotic symptoms and memory defi cits, and volumetric measures of the hippocampus, the superior temporal gyrus, and the temporal lobe in general, have been demonstrated, as well as between negative symptoms, executive function and prefrontal cortical measures (Antonova et al ., 2005 ;Gur et al ., 2007 ;Nestor et al ., 2007 ;Hurlemann et al ., 2008 ) and in particular, in relation to white matter structural integrity (Szeszko et al ., 2008 ). Th is suggests that further investigation of brain structural changes in cannabis users, in relation to symptoms and cognition, is warranted.…”
Section: Discussionmentioning
confidence: 99%